PARADIGMA BARU PEMBELAJARAN BAHASA DAN RESISTENSI MASYARAKAT TERHADAP PERUBAHAN - Imroatus Solikhah (Center of Language and Cultural Studies, 2014)
The advent of innovation in teaching English as a foreign language has taken a long practice of ideas and concepts of classroom teaching practices. An interplay of psychology of learning, classroom management, teaching procedures responding current issues in language uses and needs has promoted itinerary of teaching models. The first role of applied linguistics is prominent to place how teaching issues and its practices are perceived contextually on the track. The psychological perspectives have put learning models are viewed from various angles from which learning theories and language contents are interrelated. First major ideas deal with development of teaching methods considered traditional, e.g. grammar translation that focuses on rules, silent way that stresses problem solving learning, and communicative language teaching that emphasizes on the uses of language for real communication. The second major ideas promote innovative language teaching involving among others quantum teaching and learning, collaborative learning, effective teaching, multiple intelligences, from which language teaching methods are exposed for practices. This way, along with the development of teaching process, teaching methods are adaptive to recent trend. The resistance of language teaching method, thus, indicates flexibility of the method to absorb new needs in context.